Teachers’ attitudes towards co-curricular activities in selected schools - Yan Fang, Jane Teng; Ngee, Chuah Hong (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This study investigated the teachers’ attitudes towards co-curricular activities in schools. The aim of the paper was to highlight the teachers’ readiness, knowledge and commitment towards their involvement in co-curricular activities in schools. A total of 116 respondents participated in the survey. The findings showed that the teachers’ readiness of being involved in the activities of co-curricular was high (mean=4.00); their knowledge was found to be at high levels (mean=3.86) and their commitment was also at high levels (mean=3.86). The results of the study implied that the teachers’ attitudes towards the co-curricular activities influenced significantly the students’ performance at co-curricular activities. The students’ active participation in co-curricular activities served as the catalyst for students’ holistic development. Therefore, the teachers’ attitudes in terms of readiness, knowledge and commitment should be emphasized in curriculum planning and co-curriculum planning, implementation and evaluation.